The Influence of the Discovery Learning Model on the Ability to Analyze in Students at STKIP Taman Siswa Bima - Nurhikmah, Nurhikmah (Civiliza Publishing, Indonesia., 2025)
Discovery Learning is based on cooperative learning, students are challenged to discover and develop their own knowledge, knowing its meaning through their study groups. This study aims to determine the influence of the discovery learning model on students' ability to analyze social studies learning at STKIP Taman Siswa Bima. The type of research used is pre-experimental design. The population in the study was students at Elementary School Teacher Education semester 3 STKIP Taman Siswa Bima, with a sample of 103 students. The sampling technique used is simple cluster random sampling. The analysis technique used descriptive statistics, prerequisite test with equivalence test, homogeneity test and normality test, hypothesis test using the Paired Sample t-Test and the Independent Sample t-Test with a significance level of 0.05. The results of the study show that the Problem discovery learning model has a positive and significant effect on students' ability to analyze social studies learning at STKIP Taman Siswa Bima, based on the results of the Paired Sample t-Test, a sig value of 0.000<0.05 which means that it has an effect. The indicator that has the greatest influence is the first indicator to determine the problem with a score percentage of 95%.